Analisis Profitabilitas Pada Perusahaan yang Tergabung dalam Indeks LQ45 di Bursa Efek Indonesia - Feby Ayu Tri Ananda; Nurjanti Takarini (Universitas Serang Raya, 2021)
Profitability is a measure by which a company assesses the success of a company's management. Having a good profitability level allows the company to continue its operations and increase its value. Understanding the impact of working capital, liquidity, and firm size is the purpose of thisXresearch. In addition, this research aims to know the differences in company’s financial performance from a previous reserach, wehether it still corresponded or had undergone changes. The object of this research is the manufacturingiicompany that makes up the LQ45 stock index in the Indonesian Stock Exchange. A total of 10 companies was taken to according to saturated sampling techniques, which is taking all the parts of the population as samples. The research data to be tested comes from secondary data according to the company’s annual report published periodically in BEI. Analysis techniques used in testing research hypotheses are multiple linier regressin. The results shows the regression analysis that (1) workingXcapital, liquidity, and firm size simultaneouslyiihave a significantiieffect on profitability. (2) working capital has a significantIeffect onIprofitability. (3) liquidity and firm size have no significant effect oniprofitability. Keywords : Profitability, Working Capital, Liquidity, Firm Size